Computer science for planning, programming and balance process in sport coaching - Rivas, A. (International Journal of Computer Science in Sport, 2003)
Planning, programming and balance process in sport coaching are very important work areas for the coach and must be performed in the best way as possible. For this reason, at least, the coach has to record a lot of data from the training process and from the results of competitions. Computer science can help to these procedures in different time points and from different perspectives. Storage Problem: First we have to take into account high volume and complexity of the data the coach must manage belonging to training sessions, competitions results, medical tests and more. Computer Systems for data interpretation: An approach using Software based only on intelligent data storage would not make good use of all capabilities that a Computer System can provide. Intelligent Computer Systems for data interpretation and making decisions: Artificial Neural Nets are a useful tool for interpretation of data from the training process and competition events and its influence on final performance. An Expert Systems perspective allows to make, using rules nets, reasoning based Systems, which give the machine a small piece of knowledge from scientific demonstrations and also expert knowledge from expert elicitation.